Comprehensive Review on Main Topologies of Impedance Source Inverter Used in Electric Vehicle Applications - Daouda Mande; João Pedro Trovão; Minh Cao Ta (World Electric Vehicle Journal, 2020)
Power electronics play a fundamental role for electric transportation, renewable energy conversion and many other industrial applications. They have the ability to help achieve high efficiency and performance in power systems. However, traditional inverters such as voltage source and current source inverters present some limitations. Consequently, many research efforts have been focused on developing new power electronics converters suitable for many applications. Compared with the conventional two-stage inverter, Z-source inverter (ZSI) is a single-stage converter with lower design cost and high efficiency. It is a power electronics circuit of which the function is to convert DC input voltage to a symmetrical AC output voltage of desired magnitude and frequency. Recently, ZSIs have been widely used as a replacement for conventional two-stage inverters in the distributed generation systems. Several modifications have been carried out on ZSI to improve its performance and efficiency. This paper reviews the-state-of-art impedance source inverter main topologies and points out their applications for multisource electric vehicles. A concise review of main existing topologies is presented. The basic structural differences, advantages and limitations of each topology are illustrated. From this state-of-the-art review of impedance source inverters, the embedded quasi-Z-source inverter presents one of the promising architectures which can be used in multisource electric vehicles, with better performance and reliability. The utilization of this new topology will open the door to several development axes, with great impact on electric vehicles (EVs).